Knowledge level and the HIV/AIDS-related risk behaviors of the male prisoners in Davao City Jail - Concepcion, Albert Angelo Lancita (Animo Repository, 2000)
This is a descriptive and cross-sectional study among the male prisoners in Davao City Jail, a Bureau of Jail Management and Penology-supervised penal institution in the Philippines. The study determines the knowledge of the male prisoners on HIV/AIDS and to describe the forms of HIV/AIDS-related risk behaviors these prisoners have engaged in during incarceration. Numerous studies have already established that HIV/AIDS-related risk behaviors in various prisons worldwide included unprotected sexual intercourse with multiple partners, piercing or wounding activities with the sharing of used instruments, tattooing with the sharing of used instruments and intravenous drug use with the sharing of used needles and syringes.Data were generated from a survey of 155 randomly selected male inmates. The survey had two stages. First, all of the 155 respondents were asked to participate in order to determine how many of them have engaged in any of the risk behaviors associated with HIV/AIDS for the past twelve months at the time the survey was conducted. Secondly, the 155 respondents were further reduced to 60, which were composed of 44 male inmates who have not engaged in any HIV/AIDS-related risk behavior and 16 who have engaged in at least one risk behavior. This was done in order to compare the two groups and to ensure that the data collection process was handled more efficiently given the time and resource constraints. It was found that only less than a fourth (23.3 percent) of the respondents had a high level of knowledge about HIV/AIDS, and almost a third (31.7 percent) had an average level of knowledge and less than half (43.3 percent) had a low level of knowledge. The study also revealed that of the 16 male prisoners who engaged in HIV/AIDS-related risk behaviors during their incarceration, 13 engaged in piercing or wounding activities with the sharing of used instruments. Very few (n=2) engaged in tattooing with the sharing of used instruments, while only one engaged in unprotected orally receptive sex with multiple male partners. Intravenous drug use was an unreported activity.Bivariate analysis of the respondents' level of knowledge regarding HIV/AIDS and their HIV/AIDS-related risk behaviors in prison show that those with high level of knowledge about the disease were less likely to engage in HIV/AIDS-related risk behaviors than those with low level of knowledge. Other factors found to be related with the respondents' HIV/AIDS-related risk behaviors in prison included age, civil status, educational level, length of stay in prison, recidivism, having visitors, receiving financial support and receiving material support.It is recommended that a comprehensive, prison-based STD/HIV/AIDS education and prevention program that will provide an opportunity for learning and, eventually, one that will lead to behavior change be developed. Social and demographic factors must be considered in setting up such institution-based health programs. Discriminated and neglected groups, like the prisoners, deserve such attention.